NATIONAL PHYSICAL EDUCATION AND SPORTS SECTOR PROGRESS FORECAST USING FEDERAL STATISTICAL REPORT FORMS PROCESSED BY MODERN IT TOOLKIT - Bogomolov, G.V.; Furaev, V.A.; Vorobev, S.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to offer an IT toolkit to facilitate the management decision-making in the national physical education and sports offices at every governmental level using the standard Statistical Report Forms. Methods and structure of the study. We collected and analyzed for the purposes of the study Statistical Report Forms 1-FK, 3-AFK and 5-FK for 2015-2020 issued by the relevant municipal, regional and federal agencies – to analyze the reported socio-economic indicators versus the Sports Life Norm Project benchmarks (interim and final) [3]. The reported statistics were processed by a set of mathematical analysis and progress forecast tools using Sportstat Automated Information System (AIS) with Statistica mathematical statistics software toolkit. The Sportstat AIS processed the physical education and sports progress database for 2015-2020 available in the socio-economic section of the Statistical Report Forms, versus the Sports Life Norm Federal Project progress forecast and actual progress data. Our experts selected, for the purposes of the study, about 100 physical education and sports progress indicators from the 1-physical education, 3-adaptive physical education and 5-physical education Statistical Report Forms for the study period, to find their group correlations plus correlations with the socio-economic indicators for a few economic, health, business and other relevant sectors. Results and conclusion. The IT toolkit with an automated statistical data collection and processing capacity to facilitate the management decision-making in the national physical education and sports offices at every governmental level using the standard Statistical Report Forms offers good benefits for the efforts.